ABOUT LABOUR THERE IS EMМANOUIL CHECALIUK "GNOSIOLOGICAL POTENTIAL OF CLASSIC MECHANICS" - Мойсишин, Василь Михайлович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
In the article the question is handwritten work of the prominent Ukrainian scientist E. Checaliuk "Gnosiological potential of classic mechanics", in which first a fundamental natural law is involved in construction of classic mechanics, - general principle of conservation of energy. Some of consequences, which swim out from such conception of mechanics, differ from the consequences of both traditional mechanics of Newton and relativism mechanics of Einstein.